Implementasi Kebijakan Pengadaan Barang/Jasa Pemerintah melalui E-Procurement pada Layanan Pengadaan Secara Elektronik Kota Depok - Dendi Fatrah Ramadhan; Abdul Rahman (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
This study aims to analyze the implementation of the Government's Goods/Services Procurement Policy through E-Procurement at the Depok City Electronic Procurement Service (LPSE). This is based on several problems that occur in the procurement of goods and services in the city of Depok, such as: high cases of corruption from the types of cases of procurement of goods/services in recent years, procurement of goods and services takes a long time, there is potential fraud in the procurement process (either procurement of goods and services) in recent years. The theory of this research uses the theory of policy implementation model by Edwards III with 4 (four) indicators including: communication, resources, disposition and bureaucratic structure. The research design used is a qualitative approach with a descriptive method. Methods of data collection is done by interview, observation and documentation. This study found that the implementation of government goods/services procurement policies through e-procurement in Depok City Electronic Procurement Services was generally quite good. However, there are still several aspects that become obstacles such as: human error that causes auction failure, servers that sometimes go down, accountability for providing information on the Terms of Reference (KAK) to providers of goods/services before being published in the Electronic Procurement System (SPSE), and the potential for fraud, due to the role of the Goods/services Procurement Unit. (UKPBJ) only until the process of winning the tender. This study provides several recommendations which include: Minimizing the potential for human error by LPSE, improving server capacity and quality, increasing understanding of integrity to all employees within LPSE, and increasing the role of UKPBJ